2019
DOI: 10.1108/et-10-2018-0226
|View full text |Cite
|
Sign up to set email alerts
|

Enablers of entrepreneurial self-efficacy in a developing country

Abstract: Purpose The purpose of this paper is to investigate the factors affecting entrepreneurial self-efficacy (ESE) in a developing country (Pakistan). The literature reports that entrepreneurship education does not enhance the level of ESE of the students. In the same vein, it is strongly emphasized that self-efficacy is the basic element in the entrepreneur’s undertakings. However, limited research has been conducted on the subject and the factors that impact ESE in the context of developing economies. Design/me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 76 publications
(95 reference statements)
9
62
0
2
Order By: Relevance
“…The influence of country support on entrepreneurial self-efficacy verified in the present study is similar to that reported by Memon, et al [112], who evaluated 564 university students from Pakistan. Similar results were found in the study by Nowiński, et al [113], who evaluated 360 university students in the USA and 1054 university students in Poland.…”
Section: Discussionsupporting
confidence: 91%
“…The influence of country support on entrepreneurial self-efficacy verified in the present study is similar to that reported by Memon, et al [112], who evaluated 564 university students from Pakistan. Similar results were found in the study by Nowiński, et al [113], who evaluated 360 university students in the USA and 1054 university students in Poland.…”
Section: Discussionsupporting
confidence: 91%
“…The family environment positively and significantly affects self-efficacy, as evidenced by CR=4.898 and p-value<0.05. Research by (Mauer et al, 2017;Memon et al, 2019;Wang et al, 2018) also show similar results. A family environment provides a place for children to start their life and greatly influences their developing personalities (Ahun et al, 2017).…”
Section: Findings and Discussion Validity And Reliability Test Resultssupporting
confidence: 67%
“…Measure of instrumental readiness. Based on prior research (Kristiansen & Indarti, 2004;Ramayah & Harun, 2005;Gerba, 2012;Memon et al, 2019), access to capital was combined with access to business information, institutional environment and social networks as a one-factor namely instrumental readiness factor, with a combined measurable effect on entrepreneurial intention. Instrumental readiness factor measured by asking participants students to indicate the extent to which they consider the environmental factors could be a barrier or supporter to launching their own business.…”
Section: Methodsmentioning
confidence: 99%
“…Finally, in this part, the major environmental variable used in this study is "Instrumental Readiness". The coefficient was measured by indicators comprised capital access, business information access, institutional environment and social networks (Kristiansen & Indarti, 2004;Gerba, 2012;Mat et al, 2015;Gerba, 2012;Memon et al, 2019;Ramayah & Harun, 2005), and the following hypothesis has been developed: H4: Instrumental readiness has a positive impact on entrepreneurial intentions of university students.…”
Section: Environmental Factorsmentioning
confidence: 99%